Theoretical notes on mathematical and multiplicative thinking in the early years (Edma 0-6: Educación Matemática en la Infancia, 2021)
This article presents some conceptual meanings of mathematical and multiplicative thinking, among other concepts as relational thinking or number sense. Secondly, we do a brief review on what is known, from research, on the development of mathematical and multiplicative thinking, with an emphasis in relation to the first ages.
Keywords: Mathematical thinking; Multiplicative thinking; Early Childhood Education